2021
DOI: 10.1111/ijfs.14968
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive characteristics of collagen and gelatin extracted from Dosidicus gigas skin

Abstract: Squid skin, often discarded as processing by-product, is a good resource of collagen/gelatin. In this study, acid soluble collagen (ASC), pepsin soluble collagen (PSC) and water soluble gelatin (WSG) were extracted from squid (Dosidicus gigas) skin and physicochemically examined. The lowest yield of 33.5% was obtained for ASC extracted at 4°C, and the addition of pepsin increased the collagen yield by around 35.0% (PSC). The highest yield of 81.9% (WSG) was achieved by thermal extraction at 60°C. A low tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…The morphology of collagen is vital for assessing its potential application in biomedicine [31]. The collagen solution obtained from lizardfish scales was lyophilized, and the morphology of collagen sponges was observed by scanning electron microscopy (SEM) (Figure 3).…”
Section: Morphology Characterizationmentioning
confidence: 99%
“…The morphology of collagen is vital for assessing its potential application in biomedicine [31]. The collagen solution obtained from lizardfish scales was lyophilized, and the morphology of collagen sponges was observed by scanning electron microscopy (SEM) (Figure 3).…”
Section: Morphology Characterizationmentioning
confidence: 99%
“…Gelatine is a denatured form of collagen but differs from collagen in its chemical composition (Sun et al ., 2021), with origins from bone and skin collagen of bovine, porcine, rabbit, camel, fish, etc. (Ghaderi, Hosseini, Keyvani, & Gómez‐Guillén, 2019; Benbettaieb, Mahfoudh, Moundanga, Brachais, Chambin, & Debeaufort, 2020; Dai et al ., 2020; Huang, Tu, Sha, Wang, Hu, & Hu, 2020; Sezer, Okur, Oztop, & Alpas, 2020; Hosseini et al ., 2021).…”
Section: Affecting Factorsmentioning
confidence: 99%
“…Bone could not be completely solubilised by 0.5 M acetic acid due to high stiffness and toughness, and bone collagen also showed low solubility due to the intermolecular cross-linkages caused by hydrogen bonding through a lysine aldehyde of one chain and a hydroxylysine of an adjacent chain in the endoverlap region, resulting in the low yields of bone collagen (Li et al, 2013). Therefore, acid-solubilised and pepsinolysis-aided method was used in this study to increase the yields of LBCs and remove allergens by cleaving covalent intra-and inter-molecular crosslinkages formed by the residues of lysine and hydroxylysine, ester bonds and other bonds with saccharides at telopeptides region without affecting the tvriple helix structure (Sun et al, 2021c). Amino acid compositions (Table 1) showed that glycine (310.8-337.3 residues/1000 residues) constituted approximately 1/3 of total amino acids due to the Gly-X-Y repetitions except for the first 14 amino acid residues from the N-terminus and the first 10 amino acid residues from the C-terminus in collagen.…”
Section: Microstructure and Compositions Of Lbcsmentioning
confidence: 99%